1996
DOI: 10.1111/j.1540-8167.1996.tb00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Sock Mapping Following Monophasic and Biphasic Shocks of Equal Voltage with an Endocardial Lead System

Abstract: The decreased number of activation fronts and the longer delay following the shock for the earliest epicardial appearance of those activation fronts that do occur may be responsible for the increased defibrillation efficacy for biphasic shocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Similar results with regard to the isoelectric window and first activation location and patterns have been reported with plunge needles, 11 epicardial electrical mapping, 14,15,44 and optical mapping. 12,13 A study conduced in pigs with fiberglass plunge needles and an epicardial plaque demonstrated that a row of closely spaced fiberglass plunge needles did not substantially disrupt short duration fibrillation patterns.…”
Section: Study Limitationssupporting
confidence: 71%
“…Similar results with regard to the isoelectric window and first activation location and patterns have been reported with plunge needles, 11 epicardial electrical mapping, 14,15,44 and optical mapping. 12,13 A study conduced in pigs with fiberglass plunge needles and an epicardial plaque demonstrated that a row of closely spaced fiberglass plunge needles did not substantially disrupt short duration fibrillation patterns.…”
Section: Study Limitationssupporting
confidence: 71%
“…Using plunge electrodes to map postshock activity in dogs, Chen et al (6) determined that the location and pathway of activation fronts are markedly different from those before the shock. Additional mapping studies (3)(4)(5)26) demonstrated that the first delayed postshock activation propagates focally away from the breakthrough site. Our results are consistent with these findings.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Earliest repolarization of cycle 2 also began at apex (arrow) before repolarization of cycle 1 was complete. in vivo porcine electrical mapping studies using the same shocking electrode configuration, 4,5 activation of the first postshock cycle arose focally at the LV apex after a 78Ϯ32-ms postshock interval (65Ϯ10 ms in an electrical mapping study, 5 PϭNS) and propagated toward the base in both SDF and FDF episodes ( Figure 5). Epicardial reentry was never observed during the first postshock cycle, unlike in optical mapping studies using rabbit hearts.…”
Section: Postshock Activation Cycles and Defibrillation Outcomementioning
confidence: 99%
“…[1][2][3] Whole-heart electrical mapping of defibrillation in dogs and pigs has shown that after shocks near the defibrillation threshold (DFT) in strength, the immediate postshock activation pattern is mainly focal and is similar for both successful (SDF) and failed (FDF) defibrillation episodes. 4,5 Epicardial reentry is infrequently observed. 6 The similarity of the first postshock activations suggests that the immediate myocardial responses to the shock alone may not determine defibrillation success but rather that the first several postshock cycles may influence shock outcome.…”
mentioning
confidence: 99%